Removal of Cd2+, Cu2+, Pb2+, and Ni2+ by sludge produced from liquid crystal display glass substrate - Hong, S. H.; Lee, C. G.; Park, S. J. (International Journal of Environmental Science and Technology, 2022)
Sludge produced from liquid crystal display glass substrate (LCD-sludge) was used as an alternative treatment medium for the removal of heavy metals (Cd2+, Cu2+, Pb2+, and Ni2+) from aqueous solutions via adsorption. The elemental composition of the LCD-sludge obtained by X-ray fluorescence showed that it was mainly composed of CeO2 (26.48%), CaO (23.92%), and SiO2 (6.86%). The kinetic adsorption of Cd2+, Cu2+, Pb2+, and Ni2+ on the LCD-sludge showed that equilibrium adsorption was reached within 12 h. The maximum adsorption amounts of Cd2+, Cu2+, Pb2+, and Ni2+ on the LCD-sludge were 1.29, 8.50, 8.47, and 3.02 mg/g, respectively. The adsorption data at equilibrium for all the heavy metals were better fitted to the Freundlich than the Langmuir model. Heavy metal adsorption by the LCD-sludge was an endothermic and involuntary reaction. The effects of other cations on heavy metal removal by the LCD-sludge followed the order of Al3+ > Ca2+ > Na+. As the LCD-sludge dose was increased, the removal percentage of Cd2+, Cu2+, and Pb2+ increased, but the adsorption amount per unit mass decreased. The results suggest that LCD-sludge can be used as an adsorbent for the removal of mixed heavy metals from aqueous solutions.
Keywords: Adsorption amounts; Elemental compositions; Equilibrium adsorption; Glass substrates; Heavy metal adsorption; Heavy metal removal; Langmuir models; X ray fluorescence; Adsorption; Heavy metal; Liquid crystal display; Recycling; Sludge